HUMANISTIC PRINCIPLES IN THE PEDAGOGICAL VIEWS OF KONSTANTIN DMITRIEVICH USHINSKY - Samadova , O'g'iloy (Journal of Pedagogical and Philological Research, 2026)
This article analyzes the pedagogical views of K.D.Ushinskiy, focusing on his emphasis on humanistic principles in education and upbringing. Ushinskiy advocated for respect for the individual, compassion, equality, and justice in the learning process. He promoted a learner-centered approach, which remains relevant to contemporary education. His ideas align with modern humanistic education models.